Investigation of DC‐bus control modes and impacts on energy yield for a modular HVDC wind drive train - Lorrana Faria da Rocha; Lynn Verkroost; Hendrik Vansompel; Pål Keim Olsen (IET Renewable Power Generation)
Abstract This article aims to investigate different dc‐bus voltage balancing control modes for a modular HVDC drive train applied to offshore wind energy. The modular structure discussed consists of a stacked polyphase bridge converter connected to the modules of a segmented generator. Three voltage control modes are analysed: non‐voltage balancing, voltage balancing allowing overcurrent, and voltage balancing with power derating. Assembly imperfections and operation differences can cause parametric deviations across modules leading to generation unbalance. When operating with voltage balancing with power derating, none has ac overcurrent or dc overvoltage. However, when the turbine is already operating at nominal power, a reduction in total power is required for this to occur. On the other hand, non‐voltage balancing or voltage balancing allowing overcurrent could bring more generated power to the system as the optimal output power allows dc overvoltage or ac overcurrent in some of the modules, respectively. Therefore, there is a trade‐off between efficiency and oversizing the system's components. A sensitivity analysis is performed to identify the expected dc‐bus voltage deviation. Experimental results in a low‐power prototype validate the voltage balancing control modes and a case study demonstrates the impact on energy yield in an offshore wind turbine.